2018
DOI: 10.1016/j.exer.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocyte migration, differentiation and apoptosis during the corneal wound healing response to injury

Abstract: The aim of this study was to determine whether bone marrow-derived fibrocytes migrate into the cornea after stromal scar-producing injury and differentiate into alpha-smooth muscle actin (αSMA) + myofibroblasts. Chimeric mice expressing green fluorescent protein (GFP) bone marrow cells had fibrosis (haze)-generating irregular phototherapeutic keratectomy (PTK). Multiplex immunohistochemistry (IHC) for GFP and fibrocyte markers (CD34, CD45, and vimentin) was used to detect fibrocyte infiltration into the cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 55 publications
(80 reference statements)
0
69
0
Order By: Relevance
“…It is widely accepted that fibrocytes arise from bone marrow cells. Lassance et al, 18 demonstrate, using green fluorescent protein (GFP) chimeric mice, that cells derived from bone marrow give rise to fibrocytes that enter the cornea after injury. Similarly, in an experiment using sex-mismatched bone marrow chimeric mice (female), Mori et al 17 found the Y chromosome (from transplanted male bone marrow) in the nuclei of the majority of fibrocytes.…”
Section: Fibrocyte Originmentioning
confidence: 99%
See 4 more Smart Citations
“…It is widely accepted that fibrocytes arise from bone marrow cells. Lassance et al, 18 demonstrate, using green fluorescent protein (GFP) chimeric mice, that cells derived from bone marrow give rise to fibrocytes that enter the cornea after injury. Similarly, in an experiment using sex-mismatched bone marrow chimeric mice (female), Mori et al 17 found the Y chromosome (from transplanted male bone marrow) in the nuclei of the majority of fibrocytes.…”
Section: Fibrocyte Originmentioning
confidence: 99%
“…They conclude that fibrocytes migrate from bone marrow as predifferentiated cells-reinforcing that bone marrow is the primary location of fibrocytes differentiation. 14 Monocyte differentiation into fibrocytes has been found to take approximately 10 days in vitro, whereas fibrocytes can be found by 1 day after epithelial-stromal injury to the cornea, 18 suggesting that either local differentiation of fibrocytes from monocytes takes a shorter amount of time or they are present in the blood ready to respond to injuries by moving into tissues and Downloaded from iovs.arvojournals.org on 07/06/2020…”
Section: Fibrocyte Originmentioning
confidence: 99%
See 3 more Smart Citations